America's forgotten terrorists : the rise and fall of the Galleanists - Simon, Jeffrey D. (Jeffrey David), 1949- (Potomac Books, an imprint of the University of Nebraska Press, 2022)
"'America's Forgotten Terrorists' tells the story of a movement that nearly anticipated the era that America is currently in and what varying types of terrorism have looked like from the early twentieth century to our current state"--